2019
DOI: 10.14814/phy2.13982
|View full text |Cite
|
Sign up to set email alerts
|

No effect of beetroot juice supplementation on exercise economy and performance in recreationally active females despite increased torque production

Abstract: This study investigated the effects of acute and chronic beetroot juice (BRJ) supplementation on submaximal exercise oxygen uptake (VO 2), time trial (TT) performance, and contractile properties of the plantar flexors in females. Study 1: Using a double blind, randomized, crossover design, 12 recreationally active females using hormonal contraceptives supplemented acutely (2.5 h) and chronically (8 days) with 280 mL BRJ/d (~26 mmoles nitrate [NO3−]) or a NO3−‐free placebo (PLA). On days 1 and 8, participants c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 46 publications
3
31
0
9
Order By: Relevance
“…3 A). As has been suggested by Wickham and colleagues ( 112 ) in a recent investigation and review ( 23 ), women are heavily underrepresented in this field of research as is generally observed in biomedical research ( 116 ). Six studies that examined women only or presented data separately for women found no effect of NO 3 − supplementation on exercise performance ( P = 0.347).…”
Section: Methodsmentioning
confidence: 87%
“…3 A). As has been suggested by Wickham and colleagues ( 112 ) in a recent investigation and review ( 23 ), women are heavily underrepresented in this field of research as is generally observed in biomedical research ( 116 ). Six studies that examined women only or presented data separately for women found no effect of NO 3 − supplementation on exercise performance ( P = 0.347).…”
Section: Methodsmentioning
confidence: 87%
“…In addition to isokinetic torque, the effect of NO 3 − supplementation on different aspects of skeletal muscle contractile function is equivocal. Indeed, NO 3 − supplementation has been reported to increase force production at low stimulation frequencies in some (≤20 Hz) [ 22 , 23 , 24 ] but not all studies [ 25 , 26 ]. Although most studies have not observed an increase in maximal voluntary isometric contractile force after dietary NO 3 − supplementation [ 19 , 22 , 23 , 25 , 26 , 28 , 29 ], improved weightlifting performance [ 30 , 31 , 32 , 48 , 60 ] and concentric and eccentric contractile force during the back squat [ 61 ] have been reported after dietary NO 3 − supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of NO 3 − supplementation on involuntary electrically evoked contractions is equivocal. NO 3 − supplementation has been reported to increase force production at low stimulation frequencies in some (≤20 Hz) [ 22 , 23 , 24 ], but not all studies [ 25 , 26 ]. Although dietary NO 3 − supplementation has been reported to improve maximal voluntary contractile force during a mid-thigh pull [ 27 ], most studies have not observed an increase in maximal voluntary isometric contractile force when contracting the knee extensors [ 19 , 22 , 23 , 25 , 26 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of this work has been performed using male subjects. However, recent work from our laboratory demonstrated an improvement in skeletal muscle torque production following both acute and chronic dietary NO 3 supplementation in recreationally active females (Wickham et al 2019). This suggests that dietary NO 3 can influence skeletal muscle contractile properties in both sexes; however, the changes may not be large enough to translate into whole-body reductions in V O 2 or increases in performance in recreationally active females.…”
Section: (Ii) Contractile Efficiencymentioning
confidence: 90%
“…There was no effect of BRJ on the work completed or total V O 2 . However, V O 2 was reduced by 4% during a 5-min cooldown where the subjects cycled for 5 min at 75 W. A recent study by Wickham et al (2019) examined the effects of acute and chronic BRJ supplementation on submaximal cycling V O 2 and TT performance in 12 recreationally active females using hormonal contraceptives. The subjects supplemented acutely (2.5 h prior) and chronically (8 days) with 280 mL BRJ/day (ϳ26 mmol NO 3 -) or a NO 3 --free PL.…”
Section: Early Workmentioning
confidence: 99%